Dexrazoxane Protects Breast Cancer Patients With Diabetes From Chemotherapy-Induced Cardiotoxicity. (May 2015) - Sun, Fangyi; Qi, Xiaoyong; Geng, Cuizhi; Li, Xingtao
Abstract: Background: To evaluate the cardioprotective effect of dexrazoxane (DEX) on chemotherapy in patients with breast cancer with concurrent type 2 diabetes mellitus (DM2 ). Methods: Eighty female patients with breast cancer with DM2 were randomly assigned to receive chemotherapy only or chemotherapy plus DEX. All patients received 80 mg/m 2 epirubicin and 500 mg/m 2 cyclophosphamide by intravenous infusion every 3 weeks for a total of 6 cycles. The group assigned to receive chemotherapy alone received placebo 30 minutes before epirubicin administration. The group assigned to receive chemotherapy plus DEX received 800 mg/m 2 DEX 30 minutes before epirubicin administration. Cardiac function and hematology before and after 6 cycles of chemotherapy were analyzed. Results: There was no difference in baseline systole or diastole function between the 2 DM2 groups. Patients receiving chemotherapy alone experienced significantly greater reductions in Ea and significantly greater elevations in E/Ea and Tei index in comparison with patients receiving chemotherapy plus DEX. After chemotherapy, superoxide dismutase was significantly reduced, and serum malondialdehyde (MDA) was significantly increased in patients with DM2 . Serum superoxide dismutase levels were comparable between the 2 groups before and after chemotherapy, MDA levels were comparable between the 2 groups before chemotherapy, whereas serum MDA was significantly higher after chemotherapy in the chemotherapy alone group in comparison with the group that received DEX. Conculsions: DEX protects against cardiotoxicity induced by chemotherapy in patients with breast cancer with concurrent DM2.